From Solution to Equation

Advertisements

Topics

Notes

From Solution to Equation:

  • Equation ⇒ Solution (normal path)

  • Solution ⇒ Equation (reverse path)

Starting with x = 2.

x = 2.

Multiply both sides by 3 ⇒ 3x = 6.

Add 4 to both sides  ⇒ 3x + 4 = 10.

This has resulted in an equation. If we follow the reverse path with each step, as shown on the right, we get the solution of the equation.

Take another example,

x = 5

Multiply both sides by 3 ⇒ 3x = 15

Add 4 to both sides ⇒ 3x + 4 = 19.

If you would like to contribute notes or other learning material, please submit them using the button below.
Advertisements
Share
Notifications



      Forgot password?
Use app×